2004
DOI: 10.1111/j.1365-4632.2004.02298.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of different skin conditions in an outpatients’ setting in north‐western Nigeria

Abstract: Background Information on skin diseases in north-western Nigeria is scanty. We therefore conducted a prospective survey of 2611 new patients seen between August 1999 and July 2001 at the consultant medical / dermatology clinics of Usmanu Danfodiyo University Teaching Hospital, Sokoto, Nigeria. Methods The personal bio-data of all consecutive patients with skin diseases were documented. They were examined and the diagnoses, which were based on the history of presentation and physical examination, were recorded.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
66
4
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(100 citation statements)
references
References 16 publications
(28 reference statements)
18
66
4
1
Order By: Relevance
“…In a Yemeni study [31], the leading group of diseases was dermatitis and eczematous disorders, followed by infections and infestations (including cutaneous leishmaniasis and mycetoma), and acne and acneiform disorders. In a Nigerian study [32], infectious and parasitic diseases accounted for 44.4% of cases, eczema, acne, papulosquamous, and pigmentary skin disorders were observed in 14.1%, 7.0%, 64%, and 6.0% of cases respectively. In a study in Pakistan [33], infectious skin diseases were the commonest (60%).…”
Section: Discussionmentioning
confidence: 99%
“…In a Yemeni study [31], the leading group of diseases was dermatitis and eczematous disorders, followed by infections and infestations (including cutaneous leishmaniasis and mycetoma), and acne and acneiform disorders. In a Nigerian study [32], infectious and parasitic diseases accounted for 44.4% of cases, eczema, acne, papulosquamous, and pigmentary skin disorders were observed in 14.1%, 7.0%, 64%, and 6.0% of cases respectively. In a study in Pakistan [33], infectious skin diseases were the commonest (60%).…”
Section: Discussionmentioning
confidence: 99%
“…For example in Sokoto, Nigeria, scabies was 1.4%, while in a nearby village was 16% (24). Mycobacterial diseases (leprosy only) had less frequent rate (0.11% of the total).…”
Section: Infective Skin Diseasesmentioning
confidence: 99%
“…[19][20][21] Community-based studies in Nigeria have reported prevalence rates of skin diseases (or dermatophytoses alone) between 10% and 64%. 1,13,[22][23][24][25][26][27] The most common skin condition was fungal infections, especially tinea capitis among school-age children, especially boys, accounting for 43% of the skin diseases in the community. 1,13,22,23,25 Other common skin conditions were impetigo, 13,24 scabies, miliaria, pyoderma, 13 and tribal marks.…”
mentioning
confidence: 99%